Reinterpretation of the Nusyūz Verse in the Al-Taḥrīr wa Tanwīr Exegesis from a Mubadalah Perspective - Ulfa, Mufida; Masruri, Muhammad (UAS PRESS, 2025)
The interpretation of nusyūz verses in Muslim societies remains gender-biased. The term nusyūz gets attributed predominantly to wives rather than husbands, even though the Qur'an addresses both. This interpretive asymmetry stems from classical exegetical traditions that inadequately discuss marital relations in a balanced manner. This study re-examines Ibn 'Āsyūr's interpretation of the nusyūz verses in Tafsīr al-Taḥrīr wa al-Tanwīr through the lens of mubādalah, a hermeneutical framework emphasizing reciprocity and gender equality. Using a library research design and qualitative content analysis, this study analyzes Ibn 'Āsyūr's tafsir alongside relevant exegetical and fiqh sources. The findings reveal that Ibn 'Āsyūr's interpretation largely aligns with classical exegetes, yet introduces a significant reinterpretation of the three remedial steps for nusyūz: admonition, separation of beds, and physical discipline. Unlike most commentators who view these steps as sequential, Ibn 'Āsyūr argues that each should be applied according to the degree of marital disruption. He also emphasizes governmental intervention if a husband exceeds permissible limits. The mubādalah perspective reveals that Ibn 'Āsyūr's tafsir still lacks reciprocal and egalitarian treatment of both spouses in defining and resolving nusyūz. His interpretation requires further contextualization to align with the ethical principles of mutuality and gender justice inherent in mubādalah.